Assessing the prophylactic use of superficial inferior epigastric vessels (SIEV) for the super-drainage of deep inferior epigastric perforator flaps (DIEPs), correlated to patient demographic, anatomical and operative risk factors - Iyer, Rhea M (Clinical Surgical Oncology, 2025)
The purpose of this research is to demonstrate the benefit of SIEV inclusion and to identify the factors that deem a patient a suitable for SIEV grafting in a large patient cohort. By doing so we aim to facilitate more efficient preoperative planning and decrease the return to theatre (RTT) rates resulting from venous congestion or inappropriate SIEV use. This was a retrospective study conducted at the St. Andrew's Centre for Burns and Plastic Surgery in Broomfield Hospital, United Kingdom. 60 patients who underwent a DIEP flap reconstruction between January 1st, 2020, and December 31, 2021, were selected based on having undergone a unilateral DIEP reconstruction either with or without additional SIEV use with no other adjunct flap technique used. The patients were stratified into two cohort groups: DIEP ​+ ​SIEV use patient group (n ​= ​30) and DIEP only patients (n ​= ​30). For these patients a range of biographical data was obtained including: the presence of co – morbidities (BMI, BP, co – existing conditions such as diabetes mellitus) as well as flap characteristics (flap weight, time taken to raise the flap and the ischaemia time) from the free – flap audit forms and this was compared to anatomical data that was obtained from the pre – operative CT angiography reports detailing vascular characteristics: the Size/calibre of the SIEV (large = >3.0 ​mm, medium ​= ​2.0–3.0 ​mm and small = <2.0mm), the presence of venous anastomosis and midline crossover. The data was recorded on a spreadsheet and compared with the DIEP only group to ascertain, p – values using Chi2/Fisher's Exact Test (for non – parametric/binary data) and the Two – Tailed P – values (parametric data) where appropriate, Microsoft Excel's correlation toolkit was also used to determine the extent of correlation between the cohort groups. For non-parametric values (binary) statistical significance was present for: High BMI defined as BMI >26 ​kg/m2 (p ​= ​0.01), High BP-defined as BP ​> ​140/90 ​mmHg (P ​< ​0.01), Vein 2-IMVP (anastomosis between the second vein used whether this be a SIEV or not and the IMVP within the chest wall (p ​< ​0.00001), Large SIEV calibre – defined as >3 ​mm (p ​= ​0.015) and small SIEV calibre – defined as <2.00 ​mm (p ​= ​0.0251). The average flap weight in the DIEP ​+ ​SIEV cohort was 857.80g and in the DIEP only cohort was 641.92g (p ​= ​0.024) therefore a larger flap weight was associated with SIEV usage in our cohort. Patients presenting with these characteristics conferred a superficial venous drainage system dominance and were therefore more numerous in the DIEP ​+ ​SIEV cohort group compared to the DIEP only group. The RTT was defined to be 3-times higher in the DIEP only group and the overall cost benefit of primary SIEV use, extrapolated for the defined year period was determined to be £26,796. Our study with this limited cohort has justified the cost and clinical benefit associated with SIEV use in DIEP patients and supports its prophylactic use in patients with the characteristics defined above, to recommend its use in a more evidenced manner it would be of benefit to expand our analysis to a wider range of patients.